2023
DOI: 10.21203/rs.3.rs-3041511/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Daily Steps to Identify Older Adults with (Un)healthy Joint Profiles of Sedentary Time and Physical Activity: A Starting Point

Abstract: Herein, we investigated whether daily steps can discriminate between older adults with unhealthy and healthy joint profiles of sedentary time (ST) and moderate-to-vigorous physical activity (MVPA). Apparently healthy community-dwelling older adults aged 60–80 years were included in this cross-sectional analysis (n = 258). Daily steps, ST, and MVPA were assessed by accelerometry. Receiver Operating Characteristic (ROC) analysis was used to test the performance of daily steps in identifying older adults with unh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous research has demonstrated that daily steps can be used to identify an unhealthy combined profile of ST/MVPA in older adults. 3 However, the proposed cut-off point may not be suitable for patients with peripheral artery disease and claudication symptoms. Herein, our aim was to establish specific cut-off points for distinguishing between healthy and unhealthy combined profiles of ST/ MVPA among patients with peripheral artery disease and claudication symptoms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that daily steps can be used to identify an unhealthy combined profile of ST/MVPA in older adults. 3 However, the proposed cut-off point may not be suitable for patients with peripheral artery disease and claudication symptoms. Herein, our aim was to establish specific cut-off points for distinguishing between healthy and unhealthy combined profiles of ST/ MVPA among patients with peripheral artery disease and claudication symptoms.…”
mentioning
confidence: 99%
“…The combined profiles of ST/ MVPA were defined as follows: (i) unhealthy: highest tertile of ST and lowest tertile of MVPA; (ii) healthy: lowest tertile of ST and highest tertile of MVPA. 3 The remaining combinations were classified as 'neutral'.…”
mentioning
confidence: 99%
See 1 more Smart Citation